Ultrasonographically detected changes in Achilles tendons and self reported symptoms in elite gymnasts compared with controls - An observational study - Emerson, C.; Morrissey, D.; Perry, M.; Jalan, R. (Manual therapy, 2010)
There are no published data on the prevalence of Achilles tendinopathy in gymnasts. 40 elite gymnasts and 41 controls of mean (SD) age 16.3 (2.1) years had bilateral AT thickness (at 3 points along the tendon in longitudinal and transverse views) and abnormality measured using ultrasound (US). Data on a history of AT symptoms were gathered using a questionnaire.